Antibody-mediated encephalitis: a treatable cause of schizophrenia. - Lennox, B; Coles, A; Vincent, A (2012)
Psychiatrists need to be vigilant for the newly recognised and treatable disorder of antibody-mediated encephalitis. Psychiatric symptoms are common, and individuals with the disorder often present initially to psychiatric services. We describe the clinical features of the disorder and make recommendations for further investigations.